PENGARUH TESTIMONI, SOCIAL MEDIA, DAN CELEBRITY ENDORSEMENT TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - RR Wening Ken Widodasih; Jizenji Tyas Wirastomo; Kurbandi Satpatmantya BR (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to examine the effect of testimonials, social media, celebrity endorsements on purchasing decisions for Wardah cosmetic products among women. The method used is quantitative by using a questionnaire as a data collection tool. The sample used was 100 female respondents who bought Wardah cosmetic products in Bekasi. Data analysis was performed using multiple linear regression techniques using SPSS 25.0 software. The results of the study show that testimonials, social media, and celebrity endorsements have a significant effect on purchasing decisions for Wardah cosmetic products. Testimonials and celebrity endorsements have a bigger impact than social media. The implication of this research is that cosmetic companies can utilize testimonials and celebrity endorsements as effective marketing tools to increase product purchasing decisions. In addition, social media can also be used as an effective marketing tool, if it is chosen correctly and adjusted to the desired target market.